Value at Risk of Sukuk Ijarah and Mudharabah in Indonesia - Evi Mutia; Rahmawaty Rahmawaty; Cut Afrianandra (Journal of Accounting Research, Organization and Economics, 2018)
Objective – Sukuk is one of financial instrument that is compliant with Islamic Sharia law. Sukuk is popularly being used as a funding mechanism by the governments and corporations throughout the Muslim world and other countries. The aim of this study is to investigate risk structure of sukuk ijarah and mudharabah in Indonesia.                  Design/methodology – This study using Value at Risk (VaR) framework with an independent model analysis of t-test samples. VaR is a method of assessing the risk that uses standard statistical techniques routinely used in other technical fields. Formally, VaR is the maximum loss over a target horizon such that there is a low, pre-specified probability that the actual loss will be larger. Samples of this study were 21 companies that issued sukuk ijarah and mudharabah listed on the Indonesia Stock Exchange.Results – The results indicate that sukuk ijarah have a lower level of risk than sukuk mudharabah. By identifying the sukuk risk, it should enable stakeholders to address related funding issues.Keywords Islamic Finance, Sukuk, Ijarah, Mudharabah, Value At Risk